Pengaruh Atmosfer Toko Terhadap Keputusan Pembelian Siswa Smk Taruna Satria Pekanbaru Pada Minimarket D5mart - Wicara, Dinda Genta (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
This research was conducted on students of Taruna Satria Vocational High School Pekanbaru. The purpose of this research was to find out the effect of store atmosphere on purchase decision of students of Taruna Satria Vocational High School Pekanbaru. Data analysis techniqued used quantitative analysis. The sample selection method employed accidental sampling in which the subjects are determined accidentally from the population number who are willing to be the sample. The research samples were 90 students. Based on the simple linear regression discussion with its regression equation: Y = 0.168 + 0.736, the regression coefficient value is positive which means the more the store atmosphere given then the purchase decision will increase. The result of t test, the tcount value for store atmosphere variable is in the amount of 9.928 > ttable in the amount of 1.987. Therefore, it can be concluded that the store atmosphere variable has significant effect towards purchase decision of consumers at D5 Mart Pekanbaru. Next, it can be concluded that the store atmosphere gives contribution or effect towards the consumer purchase decision in the amount of 50.1% while the rest 49.9% is influenced by another variable that was not investigated in this research.